Implementasi Metode SMART Dengan Integrasi Telegram Pada Sistem Pemilihan Pemeran Terbaik Drama Musikal Skylite SMA Labschool Kebayoran - Maulana Muhamad Sulaiman; Sahlan; Andi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
Skylite Musical Drama is an annual event initiated by the students of SMA Labschool Kebayoran. This event is entirely student-led, with participants handling scriptwriting, choreography, stage set design, and even sponsorship acquisition independently.The selection process for the Best Actor in this musical drama is both challenging and time-consuming, as it requires a thorough evaluation to ensure the best performance. The assessment criteria include vocals, intonation, articulation, choreography, and expression.Until now, the evaluation process for selecting the Best Actor has been conducted manually, often resulting in subjective assessments due to frequently changing criteria without fixed standards. This research aims to streamline the evaluation process, automate score calculations, and minimize subjectivity in the selection process.The Simple Multi-Attribute Rating Technique (SMART) is used to calculate the candidates' scores objectively. To enhance efficiency, a web-based system has been developed and integrated with Telegram notifications to announce the final results to participants. This system significantly improves the assessment process by ensuring that calculations are based on structured evaluation attributes.